Investigation of the effect of the addition of petroleum waste to interlocking brick constituent (2011)
"Incinerator ash was investigated for its potential use as a replacement for sand and cement in concrete interlocking bricks. The physical characteristics of the raw materials were examined. Two sets of mixes were prepared. For the first set, sand and water quantities were fixed while incinerator ash was used at 0% to 100% replacement by weight for cement in steps of 10%. In the second set, incinerator ash was used at 0% to 100% replacement by weight for sand while cement and water quantities was fixed. The mixing proportions for cement, sand and water were 1:3:0.7, respectively. Compressive strength and leachability tests were performed on the specimens. Results showed that the replacement of sand by incinerator ash up to 40% exhibited higher compressive strength than the control mix (0% incinerator ash) after 28 days curing. Maximum compressive strength of 33.33N/mm2 was obtained after 28 days curing using using 20% incinerator ash substitution for sand. Replacement of cement by incinerator ash up to 20% exhibited higher compressive strength than the control mix. Compressive strength of 28.2 N/mm2 was achieved after 28 days curing period using a 20% ash substitution for cement. Leaching of heavy metals (Pb and Cd ) present in the ash was observed in concentrated nitric acid. "